Stakeholder perceptions and public health system performance evaluation: Evidence from Greece during the COVID-19 pandemic - Karokis-Mavrikos, Vassilis; Mavrikou, Maria; Yfantopoulos, John (Frontiers in Political Science, 2022)
The COVID-19 pandemic has been challenging and testing of public health systems across the globe, engaging them in a prolonged scrutinization of their functions, capacity and resources. While in theory, this process can yield invaluable insights for future policy design and mitigate future adversity, it demands a suitable mode of evaluation. Often, innovative and ambitious legislative frames are a far cry from policymaking realities plagued with institutional and operational deficiencies. As a result, we decide to move past assessments of the de jure status quo and examine the de facto modus operandi through the eyes of the systems' participating agents. We focus on the case of Greece, a country which boasts a modern public health systemic design, aligned with contemporary public health thought and international trends. We develop a new framework iteration for public health system performance evaluation, founded on prominent templates. We rely on elite surveying insights from 261 public health policy stakeholders in Greece, collected between 15.07.2020 and 13.12.2020. We capture the effect of the COVID-19 pandemic both in a latent fashion, through the timing of our survey, and in a direct one, through explicit inquiry. Our results show that the functions of the Greek Public Health System are disproportionally developed, relevant resources come to be narrow in scope and outcomes are suboptimal, failing to fulfill identified aims. Moreover, high centralization, the absence of public health expertise and undeveloped evaluative channels prevent failures from instigating adjustments. The COVID-19 pandemic has brought the system's deficiencies to light forcefully and highlighted the essentiality of scientific inputs. Our conclusions point to an ill-alignment between the system's mission and the ideational orientation of its stakeholders, which is likely to contain structural change if it remains unaddressed. We identify future research agendas and present policy directions for the Greek public health system.